Bulk and surface instabilities in boron doped float-zone samples during light induced degradation treatments. (September 2017) - Sperber, David; Graf, Alexander; Heilemann, Adrian; Herguth, Axel; Hahn, Giso
Abstract: Float-zone silicon is often used as a supposedly stable high lifetime reference material. Here it is shown, however, that boron doped float-zone samples that underwent a fast firing step may suffer from a severe degradation in bulk lifetime during illumination at elevated temperatures. Furthermore, it is observed that silicon nitride related passivation may be affected by a long-term decrease in chemical passivation quality. A time and injection resolved visualization is introduced to quickly distinguish between these degradation features. Both bulk lifetime and chemical passivation quality are shown to recover at the same treatment conditions after longer treatment times.